Principles of Plasma Diagnostics - Hutchinson, I. H (Cambridge University Press, 2002)
This book provides a systematic introduction to the physics of plasma diagnostics measurements. It develops from first principles the concepts needed to plan, execute and interpret plasma measurements, making it a suitable book for graduate students and professionals with little plasma physics background. The book will also be a valuable reference for seasoned plasma physicists, both experimental and theoretical, as well as those with an interest in space and astrophysical applications. This second edition is thoroughly revised and updated, with new sections and chapters covering recent developments in the field.